2008
DOI: 10.1017/s0007114508978272
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the form of the sesame-based diet on the absorption of lignans

Abstract: The effect of different forms of sesame-based diets on the concentration of plasma lignans was assayed by estimating the levels of certain lignans (sesame lignans and enterolignans) in the plasma of experimental animals. In a series of experiments, male Wistar rats were fed either a raw sesame-enriched diet or a tahini-enriched diet. The plasma concentration of the lignans (sesame lignans and enterolignans) was determined at various time intervals over a 24 h period after a single administration. Enterodiol an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 21 publications
(31 reference statements)
0
17
0
Order By: Relevance
“…Twenty percent of sesame or flaxseed in the experimental diets used might be considered a high amount for typical western diets. However, if consistent amount of sesame in the order of tens of grams/meal is consumed, it might be close to human intake when consuming Middle Eastern diets, where sesame can be eaten in form of spread (tahina) or dietary oil [35], although the form of the sesame preparations may affect the absorption of lignans [41]. Flaxseed can also be consumed at higher amount in far eastern diets as boiled seeds and as flour in bread or biscuits [36].…”
Section: Discussionmentioning
confidence: 99%
“…Twenty percent of sesame or flaxseed in the experimental diets used might be considered a high amount for typical western diets. However, if consistent amount of sesame in the order of tens of grams/meal is consumed, it might be close to human intake when consuming Middle Eastern diets, where sesame can be eaten in form of spread (tahina) or dietary oil [35], although the form of the sesame preparations may affect the absorption of lignans [41]. Flaxseed can also be consumed at higher amount in far eastern diets as boiled seeds and as flour in bread or biscuits [36].…”
Section: Discussionmentioning
confidence: 99%
“…17 In humans, flavonoids, such as quercetin, as well as the lignan sesamin, are absorbed in the gut, and their bioavailability is much greater than previously believed. [63][64][65] Systolic blood pressure and plasma-oxidized, low-density lipoprotein concentrations are reduced on quercetin intake in overweight subjects. 66 Recent studies have reported the powerful properties of various natural polyphenols against oxidative stress in several cellular and in vivo paradigms of neurodegenerative disease.…”
Section: Discussionmentioning
confidence: 99%
“…et al reported that the levels of enterolignans (i.e. enterolactone and enterodiole, which are the end metabolites of lignans in mammals and express strong phyto-oestrogenic activity) were increased dramatically in the plasma of Wistar rats receiving sesame for 8 weeks (26). In a same experiment on Wistar rats supplied for 8 weeks with a diet rich in sesame, Anagnostis A. et al evaluated the expression of oestrogen receptors (ERalpha and ERbeta) in the uterus tissue (27).…”
Section: Discussionmentioning
confidence: 99%